A comparative analysis of equity and balanced unit trust funds before and during covid-19 pandemic - Norhamiza Ishak; Minah Japang; Jude Woryanta Taunson (Human Resource Management Academic Research Society (HRMARS), 2022)
This paper aims to examine the comparative performance of equity and balanced unit trust funds before and during the COVID-19 pandemic, which is from January 2014 to December 2018 and January 2019 to December 2020. To achieve the aforementioned study objective, the study conducted by using three model measures, Sharpe, Treynor and Jensen’s alpha Index. The findings of this study carry out the COVID-19 pandemic does not affect the performance of equity and balanced unit trust funds. Investors gain a return from equity funds and balanced funds into a well-diversified domestic investment portfolio. To be concluded that unit trust funds help investors to put their money in different baskets of investment avenues to minimize the risk of loss of money, especially during a turbulent market. Future studies may investigate the features of fixed-income-based unit trusts, such as government and corporate bonds with commercial and social goals and as a mechanism for promoting environmental, social and governance (ESG) considerations towards establishing a low-carbon economy.